Experience in the Treatment of Irritable Bowel Syndrome Developed after a New Coronavirus Infection (COVID-19) - R. G. Myazin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study the effectiveness of Kolofort® (affinally purified antibodies to tumor necrosis factor α, to the brain-specific protein S-100 and to histamine) in patients with various variants of irritable bowel syndrome (IBS) that developed after a new coronavirus infection (COVID-19).Materials and methods. Clinical and laboratory data of 32 patients with IBS who had a history of COVID-19 pneumonia were analyzed. Course therapy with Kolofort® is prescribed according to the standard scheme for 3 months. Before and after treatment, the dynamics of the symptoms of IBS was assessed according to the questionnaire, the dynamics of anxiety was assessed according to the Hamilton scale.Results. There were a statistically significant decrease in the severity of IBS symptoms (normalization of the consistency of the stool, cessation of flatulence, a decrease in abdominal  pain; p < 0.05) and a decrease in anxiety after the end of treatment.Conclusions. Kolofort® may be effective in eliminating the symptoms of post-infectious  IBS and anxiety that developed after COVID-19.